2012
DOI: 10.21608/ajfm.2012.19540
|View full text |Cite
|
Sign up to set email alerts
|

A Clinical Study of Acute Hydrogen Cyanamide Toxicity in the Period between 2006-2009 in the Poison Control Center, Ain Shams University

Abstract: Hydrogen cyanamide is an active ingredient of Dormex® used as a plant growth regulator. Reports of the acute toxic effects of hydrogen cyanamide are limited. The emerging problem of Dormex toxicity approximately started in Egypt since 1997 and led to many deaths. Therefore, the aim of this study was to illustrate acute toxic effects of hydrogen cyanamide. Subjects and Method: The study was carried out on hydrogen cyanamide intoxicated cases presented to the poison control center (PCC), Ain Shams University Hos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…This increase in urea and creatinine induced by dormex comes in accordance with results of El Masry et al, (2000) . In previous clinical research on patients acutely intoxicated with dormex, evident nephrotoxicity was reported manifested by increase serum creatinine and blood urea level (Gamaluddin et al, 2012;Sharif and Fayed, 2021). Makris and Spanou, (2016) allocated that increased serum creatinine indicates renal injury and even at certain levels renal failure.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This increase in urea and creatinine induced by dormex comes in accordance with results of El Masry et al, (2000) . In previous clinical research on patients acutely intoxicated with dormex, evident nephrotoxicity was reported manifested by increase serum creatinine and blood urea level (Gamaluddin et al, 2012;Sharif and Fayed, 2021). Makris and Spanou, (2016) allocated that increased serum creatinine indicates renal injury and even at certain levels renal failure.…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress is known to cause hepatic, renal, and lung damage. Central nervous system, cardiovascular system, and hemopoietic system are also apparently affected (Gamaluddin et al, 2012). Dormex also suggested causing parasympathetic over-activity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…HIF-1α is a major factor regulating the cellular response to hypoxia, suggesting that hypoxia at the cellular level is associated with the encephalopathy [11] . Hypotension and shock are early symptoms observed in these patients, with a reported occurrence of 50% according to Gamaluddin H [5] . Sheshadri SH et al [12] proposed that this phenomenon may be attributed to a vasodilatory effect caused by nitro, resulting from the oxidation of hydrogen cyanamide by catalase.…”
Section: Discussionmentioning
confidence: 93%
“…Hydrogen cyanamide is highly toxic to humans and has been classified as a Class I toxicity (the highest toxicity category) by the Environmental Protection Agency (EPA) since 2003 [4] . Oral ingestion of hydrogen cyanamide poses the greatest risk, potentially leading to fatal consequences with a mortality rate of 33.3% [5] . Adverse outcomes occur in 86% of patients when the ingested dose exceeds 100 ml [2] .…”
Section: Discussionmentioning
confidence: 99%